Intense Molar Circular Dichroism in Fully Conjugated All‐Carbon Macrocyclic 1, 3‐Butadiyne Linked pseudo‐meta [2.2]Paracyclophanes. Issue 53 (3rd August 2022) - Sidler, Eric; Zwick, Patrick; Kress, Charlotte; Reznikova, Ksenia; Fuhr, Olaf; Fenske, Dieter; Mayor, Marcel
Abstract: The synthetic access to macrocyclic molecular topologies with interesting photophysical properties has greatly improved thanks to the successful implementation of organic and inorganic corner units. Based on recent reports, we realized that pseudo‐ meta [2.2]paracyclophanes (PCPs) might serve as optimal corner units for constructing 3D functional materials, owing to their efficient electronic communication, angled substituents and planar chirality. Herein, we report the synthesis, characterization and optical properties of four novel all‐carbon enantiopure macrocycles bearing three to six pseudo‐ meta PCPs linked by 1, 3‐butadiyne units. The macrocycles were obtained by a single step from enantiopure, literature‐known dialkyne pseudo‐ meta PCP and were unambiguously identified and characterized by state of the art spectroscopic methods and in part even by x‐ray crystallography. By comparing the optical properties to relevant reference compounds, it is shown that the pseudo‐ meta PCP subunit effectively elongates the conjugated system throughout the macrocyclic backbone, such that already the smallest macrocycle consisting of only three subunits reaches a polymer‐like conjugation length. Additionally, it is shown that the chiral pseudo‐ meta PCPs induce a remarkable chiroptical response in the respective macrocycles, reaching unprecedented high molar circular dichroism values for all‐carbon macrocycles of up to 1307 L mol −1  cm −1 . Abstract : Enantiopure trimeric, tetrameric, pentameric, and hexameric macrocyclic 1, 3‐butadiyne linked pseudo‐ meta [2.2]paracyclophanes were synthesized by a homocoupling reaction in high yields and their photophysical properties were analyzed. Investigating the chiroptical properties revealed unrivalled molar circular dichroism values for all‐carbon macrocycles and efficient through‐space conjugation to reach astounding polymer‐like conjugation lengths.